TP-AGB stars and stellar population properties of a post-starburst galaxy at z ∼ 2 through optical and near-infrared spectroscopy with JWST - Bevacqua, Davide; Saracco, Paolo; La Barbera, Francesco; De Marchi, Guido; De Propris, Roberto; Ditrani, Fabio R.; Gallazzi, Anna R.; Giardino, Giovanna; Marchesini, Danilo; Pasquali, Anna; Rawle, Tim D.; Spiniello, Chiara; et al. (EDP Sciences, 2025)
We present a detailed optical and near-IR (NIR) spectral analysis of J-138717, a post-starburst galaxy at z = 1.8845 observed with JWST/NIRSpec, for which we derive a stellar mass of 3.5 +/- 0.2x10(10) M-circle dot and a stellar velocity dispersion of 198 +/- 10 km s(-1). We estimate an age of similar to 0.9 Gyr and a subsolar metallicity (between -0.4 and -0.2 dex). We find generally consistent results when we fit the optical and NIR wavelength ranges separately or with different model libraries. The reconstruction of the star formation history indicates that the galaxy assembled most of its mass quickly and then quenched rapidly, similar to 0.4 Gyr before the observation. Line diagnostics suggest that the weak emission is probably powered by residual star formation (star formation rate similar to 0.2 M-circle dot yr(-1)) or a low-luminosity active galactic nucleus, without strong evidence for outflows in ionized or neutral gas. We performed a detailed study of the NIR spectral indices by comparing observations with predictions of several current stellar population models. This is unprecedented at this high redshift. In particular, the analysis of several CO and CN features argues against a strong contribution of thermally pulsating (TP) asymptotic giant branch (AGB) stars. The observations agree better with models that include very little contribution from TP-AGB stars, but they are also consistent with a mild contribution from TP-AGB stars when a younger age, consistent with the fits, is assumed. The analysis of other NIR spectral indices shows that current models struggle to reproduce the observations. This highlights the need for improved stellar population models in the NIR, especially at young ages and low metallicities. This is most relevant for studying high-redshift galaxies in the era of the JWST.